KARAKTERISTIK PETANI PADI PROVINSI RIAU DENGAN ANALISIS CLUSTER DAN BIPLOT - Nizar, Rini; Ariyanto, Anto (Jurnal Sosial Ekonomi Pertanian, 2015)
This research serves the purpose to analyze the characteristics profile of rice farmers using subsidized fertilizer with cluster and biplot analysis. By knowing the cluster characteristics we hope it can simplify in deciding subsidized fertilizer implementation policy in the effort of raising production value and farmerâs income. The sampling method used is purposive sampling where respondents is chosen by the researcherâs consideration which is rice farmerâs that have received subsidized fertilizers taken in seven Regency in Riau Province.Â Data analysis method used is cluster analysis and biplot analysis.Â The results of Rice Farmerâs Characteristic Profile Research of Riau Province can be grouped into 3 groups, the first group consists of Rokan Hulu, Kampar and Indragiri Hulu, the second group is Rokan Hikir Regency and the third group are Siak, Kuantan Singingi and Indragiri Hilir. Furthermore Based on Characteristics of implementation of subsidized fertilizers policy, gained by 4 groups that formed, first group, consists of Rokan Hulu, Rokan Hilir, Indragiri Hilir. The second group only consists of Kampar Regency, the third group consists of Indragiri Hulu and Siak, and the fourth group only consists of Kuantan Singingi Regency. Kuantan Singingi Regency is the most succesful in implementing subsidized fertilizers policy of Riau Province, for rice farmers. This research indicates exactly total amount, price, variety and time in this regency. Keywords : Biplot analysis, cluster, characteristic,subsidized fertilizers